Centaurea phrygia Linnaeus 1753 - Jarvis, Charlie (Zenodo, 2007)
Centaurea phrygia Linnaeus, Species Plantarum 2: 910. 1753. "Habitat in Helvetia, Austria, Finlandia." RCN: 6584. Type not designated. Original material: Herb. Linn. No. 1030.7 (LINN); Herb. Burser XV(2): 30 (UPS); Herb. Burser XV(2): 31 (UPS); Herb. Clifford: 422, Centaurea 12 (BM); Herb. Burser XV(2): 32 (UPS); [icon] in Clusius, Rar. Pl. Hist. 2: 6, 7. 1601. Current name: Centaurea phrygia L. (Asteraceae). : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part C), pp. 370-473 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 401, DOI: 10.5281/zenodo.291971